2023
DOI: 10.1051/shsconf/202315605003
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from Pandemic to Endemic Pedagogy: Redesigning Teaching and Learning

Abstract: COVID-19 was declared a pandemic by the World Health Organization in 2020. A year later, we consider the shift and accept the necessity of continually re-imagining blended learning for life and work in the wake of COVID-19. This paper offers strategies initiated in teaching and learning at Middle East College, Muscat, Sultanate of Oman, during and post-pandemic. This research also shows how these changes have affected students' learning. It involved three stages of Practise: Surviving during the pandemic witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The Indonesian government began implementing a hybrid learning policy while still implementing strict health protocols during the transition Children still do not get a regular learning and social environment during this transition and recovery. Thus, in addition to uncompromising health protocol services, recovery from various traumas children face during the pandemic is needed for child welfare [48][49][50][51].…”
Section: Pandemic To Endemic Covid-19 In Indonesiamentioning
confidence: 99%
“…The Indonesian government began implementing a hybrid learning policy while still implementing strict health protocols during the transition Children still do not get a regular learning and social environment during this transition and recovery. Thus, in addition to uncompromising health protocol services, recovery from various traumas children face during the pandemic is needed for child welfare [48][49][50][51].…”
Section: Pandemic To Endemic Covid-19 In Indonesiamentioning
confidence: 99%
“…While this report cited allowing student choice, accommodating for illness and quarantine, and flexibility if the university switched from open to closed campus as reasons for adopting HyFlex format, student perceptions were not included [11]. In another study examining the entire student body of a civil engineering program in the spring semesters of 2020, 2021, and 2022, which had online, online, and blended formats respectively, it was found that overall student rankings of the program dropped to 3.8 out of 5 in the spring semester of 2020, then rose to 4.1 for the two following academic years, while satisfaction with the teacher and teaching materials rose each year [12]. Again, more detailed analysis of student perceptions was not included [12].…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned study involving freshman mathematics students found that grades were significantly higher for female students from underrepresented minority groups taking the course in virtual format and were not significantly different for all other groups [9]. The civil engineering program study found that performance varied by level, with scores of level 1 students decreasing over the three years of the study and scores for level 3 students increasing over that same time interval [12]. Another study examined the relationships between attendance mode, student personality traits, and academic integrity [13].…”
Section: Introductionmentioning
confidence: 99%